Christian beginnings : from Nazareth to Nicaea, (AD 30-325) - Vermes, Geza, 1924- (London : Allen Lane, 2012)
The creation of the Christian Church is one of the most important stories in the development of the world's history, but also one of the most enigmatic and little understood, shrouded in mystery and misunderstanding. With a forensic, brilliant re-examination of all the key surviving texts of early Christianity, Geza Vermes illuminates the origins of a faith and traces the evolution of the figure of Jesus from the man he was - a prophet fully recognisable as the successor to other Jewish holy men of the Old Testament - to what he came to represent: a mysterious, otherworldly being at the heart of a major new religion.
Machine generated contents note: 1.Charismatic Judaism from Moses to Jesus -- 2.The Charismatic Religion of Jesus -- 3.Nascent Charismatic Christianity -- 4.The Christianity of Paul -- 5.Johannine Christianity -- 6.The Didache and Barnabas -- 7.The Apostolic Fathers: 1 and 2 Clement, Ignatius, Polycarp, Hermas and Diognetus -- 8.Apologists and Theologians of the Second Century: Justin, Melito and Irenaeus -- 9.Three Pillars of Wisdom: Tertullian, Clement of Alexandria and Origen -- 10.Nicaea: Eusebius of Caesarea, Arius and Constantine -- 11.From Charisma to Dogma - A Bird's Eye View.
Includes bibliography (p. 245-256) and index.
Keywords: Jesus Christ; Church history -- Primitive and early church, ca. 30-600.; Christianity